Teoria partycypacji w myśli Grzegorza Palamasa - Palusińska, Anna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
Gregory Palamas creates philosophical and theological synthesis, which originates from his own mystical experience of hesychasm. Palamas claims that man can participate in non created, eternal energeiai of God, which are the external activities ofGod’s uosia – essence. Palamas says that all things participate in God, and they are constituted by this participation, they do not, however, participate in His nature, but in Hisactivity. A man participates in God’s eternal activities and in this way can achieve moral and ontic perfectness.